Optimizing Tax Compliance: Understanding the Link Between Company Tax Administration and Tax Avoidance (A Survey of Public Companies in Indonesia, Malaysia, Singapore, and Thailand for the 2022–2023 Period) - Arie Pratama; Kamaruzzaman Muhammad (Economies)
Tax compliance remains a critical issue in corporate taxation research, particularly in understanding the causal link between the administration of corporate tax and tax avoidance. This study investigates the potential simultaneous relationship between the two by analyzing 277 listed firms across four Southeast Asian countries using two-year average data (2022–2023). The administration of corporate tax is measured using eight disclosure-based indicators from the Refinitiv Eikon database, while tax avoidance is proxied by the effective tax rate (ETR). The primary analysis applies multiple regression to assess the effect of tax administration on tax avoidance and logistic regression to evaluate the reverse relationship. To address endogeneity and test for simultaneity, robustness checks using two-stage least squares (2SLS) and instrumental variable techniques are employed. The results confirm a bidirectional relationship: a stronger administration of corporate tax is associated with lower tax avoidance, while tax avoidance behavior also shapes tax administration practices. These findings underscore the importance of strengthening internal tax governance as a foundation for compliance. Given varying levels of tax administration across countries, this study calls for greater international coordination to standardize corporate tax governance practices and reduce avoidance incentives.